In Their Own Words: Young Adults' Menthol Cigarette Initiation, Perceptions, Experiences and Regulation Perspectives. Issue 9 (17th February 2017) - Wackowski, Olivia A; Evans, Kiameesha R; Harrell, Melissa B; Loukas, Alexandra; Lewis, M Jane; Delnevo, Cristine D; Perry, Cheryl L
Abstract: Background: Menthol cigarettes are disproportionately used by young people and have been called smoking starter products. However, limited qualitative research exists on young adults' perceptions of and experiences with these products, with much of it based on document reviews of the tobacco industry's research. Methods: We conducted six focus groups with young adult (ages 18–24) menthol smokers in New Jersey (half with black smokers) between December 2014 and March 2015. Participants were asked open-ended questions about their menthol smoking initiation, preference reasons, substitution behaviors, and perceptions of menthol cigarette risks and regulation. Results: Participants' menthol cigarette initiation and preference were influenced by their perceived popularity, brand recognition, taste, smoothness, satisfaction and access (including as "loosies, " typically available for Newport). Some believed menthol cigarettes were less harmful than non-menthol cigarettes when initiating smoking. Many currently believed menthol cigarettes were more harmful because they contained extra "additives, " were stronger (ie, requiring fewer cigarettes to feel satisfied), and/or based on hearsay. Many had tried new brand Camel Crush, which was perceived to be especially minty, fun, and attractive for newer smokers. While some used non-menthol cigarettes when menthols were unavailable, many said they would never or almost never substitute. Many acknowledged a menthol cigarettes ban would likely help them quit smoking, even though they did not support the idea. Conclusions: Menthol cigarette initiation is influenced by an interplay of multiple factors including their sensory properties, marketing, perceived popularity and availability. The FDA should continue to pursue closing this flavored cigarette loophole. Implications: In this first qualitative study of menthol cigarette use among young adults, we found further evidence that menthol cigarettes can act as starter products because they are perceived as easier to smoke and taste and smell better than non-menthol cigarettes. We also add to the literature in finding that menthol cigarettes are perceived by young people who smoke menthol cigarettes as delivering satisfaction with fewer cigarettes, being accessible as "loosies", and being popular among their peers. Many did not understand the reasons behind a potential menthol ban. Any future regulation of menthol cigarettes should include a public educational campaign to support buy-in.